Analisis Pola Kalimat Majemuk Bertingkat pada Karya Ilmiah dalam Buku Cerdas Cergas Berbahasa dan Bersastra Indonesia SMA/SMK Kelas XI Kurikulum Merdeka (International Forum of Researchers and Lecturers, 2023)
In the paragraphs of scientific writings, it is possible to find multilevel compound sentences, namely sentences consisting of one basic sentence that acts as the core and one or many other basic sentences that also act as subordinate clauses. Thus, the writing team was moved to carry out an analysis of multilevel compound sentences. The purpose of this analysis is to examine or dissect multilevel compound sentences, both in the use of variations in patterns and sequences of clauses and their descriptions. A qualitative, descriptive approach is the method used in this analysis. The data used in this analysis comes from scientific papers entitled